PSY's slated appearance draws flak - Daily Express, (KK) (Daily Ekspress (kk), 2013)
PETALING JAYA: Several politicians and analysts are questioning the motive of BN to bring South Korean' star PSY of Gangnam Style fame at the Chinese New Year open house which is said to cost nothing less than RM1 million.